Pos Laju MY’s Courier Management by Employee Efficiency Issues - Edum, Enedy Edward; Kee, Daisy Mui Hung; Zulkifli, Muhammad Harith; Noorazmi, Norain Natasha; Hamizi, Siti Murni; Almutairi, Ahmad (AIBPM Publisher, 2019)
This research about Pos Malaysia which is one of the famous postal delivery services in Malaysia. The purpose of this research to study about employee ethics and management in Pos Malaysia that provide postal services of letters, parcels and others to their customers. Good management and efficient service are need to fulfill their customers satisfaction and wants. Especially during nowadays, the demand of postal service increases with the new type of selling which is online shopping or known as E-commerce business. This research also discusses about the strategies to maximize Pos Malaysia’s profit. In addition, feedback and complains need to take as a motivation to be successful organization. The modifications make by Pos Malaysia according to their customers feedback may help the company to improve their services and fulfill their customer needs. In conclusion, our hope doing this research to increase our learning, knowledge and help Pos Malaysia to be the most excellent postal delivery service either in Malaysia or in the world. Keywords: ethics, employee, management, postal services, customer needs, demand, Ecommerce, maximize profit, feedback, improvement